2015
DOI: 10.1080/01652176.2015.1027039
|View full text |Cite
|
Sign up to set email alerts
|

Acylcarnitine ester utilization by the hindlimb of warmblood horses at rest and following low intensity exercise and carnitine supplementation

Abstract: Background: Acylcarnitines play an important role in fuel metabolism in skeletal muscle. Objective: To assess acylcarnitine ester utilization by the hindlimb of horses at rest and following low intensity exercise and carnitine supplementation. Animals and methods: Acylcarnitine ester uptake by the hindlimb was investigated using the arteriovenous difference technique. Blood from six warmblood mares (mean age 12 § 3 (SD) years and weighing 538 § 39 kg) was collected simultaneously from the transverse facial art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It has been reported that elevation in plasma fatty acid availability prior to exercise could reduce utilization of muscle glycogen (Brass & Hiatt, 1998;Smith et al, 2008), which promotes an important pathway to spare glycogen stores (Wall et al, 2013;Brass & Hiatt, 1998;Kashef & Saei, 2017) and subsequent improvement in endurance capacity. However, the fatty acid oxidation ratio is decreased when an exercise intensity exceeds 70% VO 2max (Wall et al, 2013), and glycolysis is increased (Peters et al, 2015;Wall al., 2013). This results in depletion of glycogen stores and subsequent exercise cessation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that elevation in plasma fatty acid availability prior to exercise could reduce utilization of muscle glycogen (Brass & Hiatt, 1998;Smith et al, 2008), which promotes an important pathway to spare glycogen stores (Wall et al, 2013;Brass & Hiatt, 1998;Kashef & Saei, 2017) and subsequent improvement in endurance capacity. However, the fatty acid oxidation ratio is decreased when an exercise intensity exceeds 70% VO 2max (Wall et al, 2013), and glycolysis is increased (Peters et al, 2015;Wall al., 2013). This results in depletion of glycogen stores and subsequent exercise cessation.…”
Section: Discussionmentioning
confidence: 99%
“…This results in depletion of glycogen stores and subsequent exercise cessation. In-line, L -carnitine is an indispensable compound for mitochondrial energy source by transporting long-chain fatty acids across the mitochondrial inner membrane as acyl-carnitine esters (Peters et al, 2015;Siddiqui et al, 2015), by regulating COA homeostasis (Miklos et al, 2016), by buffering toxic acyl-COA (Broad et al, 2006;Peters et al, 2015), by serving as a source of acetyl-L -carnitine, acetylcholine, and L -glutamate, in which they contribute to energy-producing reactions (Zhang et al, 2012), and by stimulating nitric oxide production (Miklos et al, 2016), in which it enhances pulmonary gas exchange and acts as a vasodilator and therefore increased blood flow (Verges, Flore, Favri-Juvin, Lévy, & Wuyam, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation